2022
DOI: 10.3390/nu14122507
|View full text |Cite
|
Sign up to set email alerts
|

Diet Is a Stronger Covariate than Exercise in Determining Gut Microbial Richness and Diversity

Abstract: Obesity is a common metabolic disorder caused by a sedentary lifestyle, and a high-fat and a high-glucose diet in the form of fast foods. High-fat diet-induced obesity is a major cause of diabetes and cardiovascular diseases, whereas exercise and physical activity can ameliorate these disorders. Moreover, exercise and the gut microbiota are known to be interconnected, since exercise can increase the gut microbial diversity and contribute to the beneficial health effects. In this context, we analyzed the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…By changing the amount or composition of lipids entering the colon, the altered digestion and absorption of fat caused by ingested PE-I could also impact the gut microbiome. A high fat diet has been shown to rapidly and reversibly alter the gut microbiota in mice , and is frequently used to induce obesity, typically accompanied by gut dysbiosis, in experimental animals. As summarized in recent reviews, although interventional changes in dietary fat have not been found to consistently alter the gut microbiome composition in humans, several observational studies have reported an inverse correlation between fat intake and gut microbiota diversity in humans. ,, Moreover, gut dysbiosis has been implicated in neuro-psychiatric disorders that often accompany obesity, which are thought to be mediated by the activity of the gut microbiota through the “microbiota-gut-brain axis”, recently reviewed by Cryan et al and Morais et al Reduced lipid delivery to the colon due to increased absorption in the presence of PE-I might therefore improve the diversity of the gut microbiome and thereby ameliorate these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…By changing the amount or composition of lipids entering the colon, the altered digestion and absorption of fat caused by ingested PE-I could also impact the gut microbiome. A high fat diet has been shown to rapidly and reversibly alter the gut microbiota in mice , and is frequently used to induce obesity, typically accompanied by gut dysbiosis, in experimental animals. As summarized in recent reviews, although interventional changes in dietary fat have not been found to consistently alter the gut microbiome composition in humans, several observational studies have reported an inverse correlation between fat intake and gut microbiota diversity in humans. ,, Moreover, gut dysbiosis has been implicated in neuro-psychiatric disorders that often accompany obesity, which are thought to be mediated by the activity of the gut microbiota through the “microbiota-gut-brain axis”, recently reviewed by Cryan et al and Morais et al Reduced lipid delivery to the colon due to increased absorption in the presence of PE-I might therefore improve the diversity of the gut microbiome and thereby ameliorate these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One of these was Butyricimonas , which belongs to the Bacteroidetes phylum and was more abundant in the group with poorer HEIs. This genus has been positively associated with the adoption of a high-fat diet [158], but also with normal BMIs in another study [159]. Moreover, the B. virosa species has previously been stated to have a beneficial effect on obesity and T2D by promoting SCFA production [160] and thus the secretion of the glucagon-like peptide-1 (GLP-1) [161], an incretin that activates glucose-dependent insulin secretion and inhibits glucagon release [162].…”
Section: Discussionmentioning
confidence: 99%
“…There were many changes in taxa identified, including higher Proteobacteria with high-fat feeding. The increase in diversity was suggested to be consistent with an induction of bacteria that metabolize carbohydrates, perhaps as a compensatory mechanism [37 ▪ ].…”
Section: Dietary Patterns and Diet Components Associated With A Benef...mentioning
confidence: 93%
“…In one study that evaluated high fat diets and exercise in mice using a 2 × 2 study design, the effects of diet on the intestinal microbiota were found to be much more profound than that of exercise [37 ▪ ]. The two groups of mice fed the high fat diet had lower Bacteroidetes to Firmicutes ratios and gut microbial richness than the mice fed the chow diet, regardless of whether or not the mice were exercised on a treadmill [37 ▪ ]. However, mice in the two high-fat diet groups had higher diversity (Shannon) and evenness.…”
Section: Dietary Patterns and Diet Components Associated With A Benef...mentioning
confidence: 99%